Value-Orientation Differentiation of Volunteers-Educating of the Internet Encyclopedia "Wikipedia" and the Project "Otvety." Part 2 - Evgeniy A. Bryzgalin; Alexander E. Voiskounsky; Stanislav A. Kozlovskiy (Peoples' Friendship University of Russia (RUDN University), 2022)
Over the past decades, altruistic cyber activities of online education volunteers who share useful knowledge with other Internet users have become widespread in the Internet space. Personal and group features of such prosocial behavior, which is strongly influenced by the realization of values, have not been sufficiently studied by psychological science so far. This study continues the psychological analysis of the value-orientation sphere of online educators, focusing on competent education volunteers who deal with the Internet encyclopedia "Wikipedia" (N = 92) and the question-answer (QA) online project "Otvety" (N = 113). The following tools were used in the work: the revised Portrait Value Questionnaire (PVQ-R2R) by Sh. Schwartz adapted by T.P. Butenko, D.S. Sedova and A.S. Lipatova and the Value Orientations Techniques developed by O.I. Motkov and T.A. Ogneva (version 2). The results of the analysis provide sufficient grounds to characterize the members of both groups as indivi- duals who are productively oriented towards informational and pro-social Internet activities that are not identical in format from the perspective of transfinite altruism, for the implementation of which optimal non-hierarchical-parity conditions have been created in their reference online communities, stimulating liberty in the process of individual self-realization. It is shown that, with a high homogeneity of the value profiles of the Wikipedia authors and QA "Otvety" service experts, the internal value-related self-determination (procedural in nature) has a basal meaning for them, since the external one, set in a heteronomous position, only weakly corresponds to their freedom-seeking way of life. It is concluded that the series of theoretical and empirical psychological studies of the diverse teams of online education volunteers will make it possible, by understanding their personal and group specifics, to lay a solid foundation, which can potentially lead to global unity of people with the prospect of large-scale amplification of knowledge as one of the highest human values.